The Analysis of Illocution Functions for Imperative Utterances in Uncle’s Tom Cabin - Agus Dimyati Masykur (Universitas Veteran Bangun Nusantara, 2022)
This study aims to identify and describe the kinds of illocutionary functions for imperative utterances in the novel “Uncle Tom's Cabin” by appliying pragmatic approach. it used a descriptive qualitative method with embedded case study. The data consists of the form of words, phrases and sentences containing speech acts that have an illocutionary power functioning as imperative obtained from all dialogues in the novel. After that, the data were collected by content analysis method. The result reveals that there are 35 data which have function for commanding and then followed by 28 data for requesting. Then, there are also 17 data for suggesting, 13 advicing data, and 3 complaining data. At last, there are both of recommending and promising having 2 data in this research. In the conclusion, the function of commanding is tend to be discovered dominantly in this research since this novel tells about slavery issue.